THE DEVELOPMENT OF TRAINING MODEL OF WEB ENHANCE LEARNING in COMPUTER PROGRAMMING (WELComP) RESULTING IN BASIC PROGRAMMER COMPETENCE (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Education has a role in creating quality human resources which is the main capital in development and are an investment to prepare humans to have the capacity for creativity, productivity, and competitiveness in encountering the environment of the digital revolution 4.0 era. However, formal education only is not enough to improve the quality of graduates. Training needs to be implemented as well in order to provide a better competency ability. The selection of appropriate training approaches, models, and strategies is one of the efforts to achieve successful training in order to achieve competency standards in accordance with training objectives. Active, creative, and innovative learning process innovation is the key to successful training. The WebEnhanced Learning in Computer Programming (WELComP) training model is a model produced in Research and Development (R&D). This study was designed using the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) development model. The development was carried out in collaboration with the scientific approach, the discovery learning model, and the demonstration learning method. This research aimed to produce and improve the competence of a Basic Programmer. The feasibility of the WELComP training model to be applied to training activities was proven by the validity test results conducted using Aiken's V formula. The V value obtained was 0.771, which is in the range 0 < V < 1.00 and greater than 0.677, thus it is indicated as a fairly high coefficient and considered valid. The validity test indicates that the WELComP training model can be used in training as an effort to produce basic programmer competencies.